Geriatric care‐related outcomes in patients 75 years and older admitted to a pulmonary disease center and predictors for hospital‐related complications - Daniela Josefina Cataneo‐Piña; Celia Gabriela Hernández‐Favela; Lidia Aurora Mondragón‐Posadas; Citlalic Torres Nuñez (Aging Medicine, 2023)
Abstract Objective The primary aim of this study was to evaluate the influence of targeted interventions, administered through comprehensive geriatric assessments on the incidence of hospitalization‐related complications among older adults diagnosed with pulmonary diseases. Methods A retrospective analysis of medical records encompassed individuals aged 75 years and older who were admitted to a lung center during the period spanning from March to June 2023. These admissions occurred in a context where standardized geriatric management protocols were systematically implemented. This study's scope extended to assessing the prevalence of hospital‐related complications, encompassing delirium and pressure ulcers. A rigorous multivariate logistic regression analysis was conducted to discern and characterize associated factors. Results The integration of comprehensive geriatric assessment yielded a substantial reduction in in‐hospital complications among the cohort of 118 patients (mean age : 82.1 ± 5.6 years, 44.5% women). The incidence of delirium decreased from 53.3% to 21.8% [odds ratio (OR): 0.246, 95% confidence interval (CI): 0.134–0.450, p < 0.001], whereas the presence of pressure ulcers decreased from 43.9% to 25% (OR: 0.395, 95% CI: 0.217–0.715, p < 0.001). The multivariate analysis uncovered independent associations between delirium and variables including community‐acquired pneumonia (OR: 4.417, 95% CI : 1.574–12.395, p = 0.005), severe disability (OR: 2.981, 95% CI: 1.140–7.798, p = 0.026), and hearing loss (OR: 3.219, 95% CI : 1.260–8.170, p = 0.014). Prolonged hospital stays emerged as the sole factor significantly associated with pressure ulcers (OR: 1.071, 95% CI: 1.033–1.109). Furthermore, an intricate bidirectional relationship was evident between delirium and pressure ulcers (OR: 7.158, 95% CI: 2.962–17.300, p < 0.01). Conclusion In conjunction with its consequent interventions, geriatric evaluation assumes a pivotal role in ameliorating adverse outcomes stemming from hospitalization among older adults afflicted with pulmonary ailments. This role gains particular salience among subpopulations characterized by heightened susceptibility, such as individuals coping with hearing loss and severe disability.